A variant of the venom allergen-like protein, DdVAP2, is required for the migratory endoparasitic plant nematode Ditylenchus destructor parasitism of plants - Chang, Qing; Yang, Yiwei; Hong, Bo; Zhao, Yanqun; Zhao, Mengxin; Han, Shanshan; Zhang, Feng; Peng, Huan; Peng, Deliang; Li, Yingmei (Frontiers in Plant Science, 2023)
The potato rot nematode, Ditylenchus destructor, poses a serious threat to numerous root and tuber crops, yet the functional characterization of effectors from this migratory endoparasitic plant nematode remains limited. Despite inhabiting distinct habitats, sedentary and migratory plant parasitic nematodes share the structurally conserved effectors, such as venom allergen-like proteins (VAPs). In this study, a variant of DdVAP2 was cloned from D. destructor. The transcription profile analysis revealed that DdVAP2 was higher expressed in D. destructor feeding on either potato or sweet potato compared to on fungus via qRT-PCR. And DdVAP2 was highly expressed at all life stages feeding on sweet potato, except for eggs. DdVAP2 was confirmed to be specifically expressed in the subventral esophageal glands of D. destructor through in situ hybridization assays. Combined with functional validation of the signal peptide of DdVAP2, it suggested that DdVAP2 could be secreted from nematode into host. Heterologous expression of DdVAP2 in Nicotiana benthamiana revealed that the protein localized in both cytosol and nuclei of plant cells. Knocking down DdVAP2 by RNAi in D. destructor resulted in infection and reproduction defects on plants. All the results suggest that DdVAP2 plays a crucial role in the interaction between D. destructor and plants by facilitating the nematode infection.